A Study on the Effects of Hybridized Metal Oxide and Carbonaceous Nano-Cutting Fluids in the End Milling of AA6082 Aluminum Alloy - Vignesh S; Mohammed Iqbal U; Jaharah A. Ghani (Lubricants, 2023)
Finding an alternate solution for supplanting the existing conventional lubricant in machining is a challenge. This work narrows the search down to the use of nano-cutting fluids, as they exhibit excellent properties such as high thermal conductivity and good lubricity. A technical analysis of the performance of hybrid nano-cutting fluids in the end milling of AA6082 aluminium alloy in a constrained end milling condition is presented. Alumina and carbon nanotubes were chosen in this study for their better physical characteristics and compatibility during machining. Coconut oil was chosen as the base fluid (dispersal medium) as it provides good lubricity and better dispersion of nanoparticles due to its excellent rheological behaviour. The hybrid nanofluid was prepared by mixing alumina-based nanofluid with carbon nanotube nanoparticles in different volumetric concentrations. The thermo-physical properties of the prepared hybrid nanofluid were tested. Furthermore, they were tested for their spread-ability and other mechanical properties. Later, their performances as cutting fluid were studied with the minimum quantity lubrication (MQL) technique, wherein nanoparticle mist was formed and evaluated in the end milling of AA6082 aluminium to reduce the quantity of nanofluids’ usage during end milling. The controllable parameters of speed, feed rate, and type of cutting fluid were chosen, with the levels of cutting speeds and feed rate at 75–125 m/min, and 0.005–0.015 mm/tooth, respectively, and the response parameters studied were surface roughness and tool wear. The results show that better performance is achieved in hybridized nano-cutting fluid, with a sharp improvement of 20%, and 25% in tool wear and surface roughness when compared to the base fluid. This study has explored the concept of hybridization and the capability of nanofluids as cutting fluids that can be used as eco-friendly cutting fluids in manufacturing industries.